Caracterização mineralógica e da matéria orgânica do solo por técnicas espectroscópicas e DRX - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2009)
Organic matter is the main agent present in the soil due to some of its actions, for example: responsible by source of nutrient for the plants, avoid erosive process, improve the aggregates stability, and act as a drain to atmospheric CO2, among others. Therefore, there are same management practice to enforce an increase in the percentage of soil organic matter, increasing the soil quality and the fertility. Among the management systems uses, being conservation management system that increase or keep the same rate of organic matter mainly on the surface, and Conventional Management that use a high rotation and cleanup the soil. In this work were used samples of Distrofic Red Latossol from Ponta Grossa – PR region, at different management systems: Conventional Tillage (CT), Reduced Tillage (RT) and No-Tillage (NT) at 0-5, 5-10, 10-15 and 15-20 cm of depth. Beyond the samples without any treatment (whole soil) it was analyzed parts obtained by granulometric physical fraction according: smaller than 2 μm (clay), between 2-20 μm (silt) and between 20-1000 μm (sand). All the samples were analyzed by X-ray fluorescent (XRF) and Fourier transform infrared (FTIR) and X-ray diffraction. It was determined eleven different mineral in the samples: Cau, Ha, Mt, Gb, Ve, An, Gt, Qz, He, Mag ant Rt. In relation to management systems and depth were not find qualitative different at the minerals. Humification indexes was determined in the soil organic matter by laser induced fluorescent (LIF) and the C/N ratio. CT samples showed larger humification and lower C/N ratio than others systems. In the other hand, NT collected between 0-5 cm depths showed larger percentage of C and lower humification than others systems. Sand fraction showed larger humification than other fractions soil studied. All cases presented lower humification in the superficial samples (0-5 cm depth). NT samples showed more favorable for organic matters accumulated, it was observed due to the difficult to separate the sand fraction from the others fractions by the granulometric physical fraction.
Keywords: humificação; FIL; minerais; humification; LIF; minerals; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA